2017
DOI: 10.1089/apc.2017.0147
|View full text |Cite
|
Sign up to set email alerts
|

HIV Care Providers' Intentions to Prescribe and Actual Prescription of Pre-Exposure Prophylaxis to At-Risk Adolescents and Adults

Abstract: Pre-exposure prophylaxis (PrEP) is indicated for use in US adults, and little is known about clinician intentions to prescribe and actual prescription of PrEP to adolescents younger than 18. Fifty-six clinicians who care for HIV-infected and at-risk youth completed an anonymous online survey in 2014. Primary outcomes were (1) intentions to prescribe PrEP to adolescents and adults in four risk categories [men who have sex with men (MSM), transgender women, heterosexuals with multiple partners of unknown HIV sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 38 publications
(47 reference statements)
1
41
0
Order By: Relevance
“…It is important to note that structural obstacles to care, including provider availability and perceptions, uninsurance, and underinsurance, will persist even after new modalities become available. 33,34 Among our study sample, the SI was the most frequently ranked first PrEP formulation choice, followed by the LAI, daily oral pill, RM, and AI. Formulation rankings suggest that both the SI and LAI are preferred over daily oral PrEP.…”
Section: Discussionmentioning
confidence: 93%
“…It is important to note that structural obstacles to care, including provider availability and perceptions, uninsurance, and underinsurance, will persist even after new modalities become available. 33,34 Among our study sample, the SI was the most frequently ranked first PrEP formulation choice, followed by the LAI, daily oral pill, RM, and AI. Formulation rankings suggest that both the SI and LAI are preferred over daily oral PrEP.…”
Section: Discussionmentioning
confidence: 93%
“…Studies have shown that primary care providers are more willing to discuss PrEP with MSM than PWID, 59 while nurse practitioners may be more willing to prescribe PrEP to heterosexuals. 60 However, due to stigma and resulting reluctance to attend medical appointments, 56 PWID may have limited contact with primary care providers, and addiction specialists may have low knowledge of, or ambivalence about, PrEP. 61 Improving providers' knowledge, comfort, and willingness to discuss PrEP and sensitive HIV risk behaviors (both sexual and injection-related) with PWID will also be required to promote PrEP uptake in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 28 articles included in our systematic review, 18 studies reported lack of provider knowledge as a barrier to PrEP prescription. 24,[26][27][28]31,32,34,38,[40][41][42][43][44][45][46][47]49 PrEP awareness among PCPs increased steadily, from 24% to 66% between 2009 and 2015. 44 However, PrEP knowledge remained low, with only 17% of providers indicating that they had read the CDC guidelines in 2014.…”
Section: Lack Of Knowledgementioning
confidence: 99%
“…28 However, one study found that lower endorsement of cost and insurance factors was associated with higher intentions to prescribe PrEP. 40…”
Section: Concerns About Costmentioning
confidence: 99%